Fibrinogen-to-albumin ratio (FAR) for predicting microvascular flap complications in reconstructive surgery - Rihards Peteris Rocans; Janis Zarins; Evita Bine; Insana Mahauri; Renars Deksnis; Margarita Citovica; Simona Donina; Indulis Vanags; Biruta Mamaja (JPRAS Open)
Summary: Background: Microvascular flap surgery is a widely used procedure for the reconstruction of various defects. Data on laboratory biomarkers for the prediction of flap complications are currently limited. We aimed to investigate the link between preoperative fibrinogen-to-albumin ratio (FAR) and various flap complications. Methods: This prospective cohort study included 130 adult patients who underwent elective microvascular flap surgery. Preoperative blood samples for the analysis of plasma fibrinogen (g/L) and albumin (g/L) were collected on the day of surgery before initiating crystalloid infusion. Post-operative data on various flap complications were obtained. Results: The overall complication rate was 17.7% with true flap loss occurring in 5.4%. Binary logistic regression revealed that the patients with FAR<0.08 and FAR<0.06 had increased odds of flap hematoma or flap loss (OR 3.68 [1.04-13.03], p=0.044 and 6.01 [1.71-21.08], p=0.005). Patients with FAR>0.10 had increased odds of minor flap complications (OR 5.47 [1.33-22.50], p=0.019). Patients with FAR<0.06 had increased odds of any flap complications (OR 4.71 [1.27-18.03], p=0.021). Patients with FAR>0.10 also had increased odds of any flap complications (OR 3.09 [1.08-8.81], p=0.035), implying a U-shaped link. Conclusions: Assessment of FAR to estimate the risk of complications has considerable predictive value in microvascular flap surgery. Patients undergoing this surgery can be evaluated to predict their nutrition and coagulation risks and optimize decision-making in their perioperative care.